2021
DOI: 10.1088/1751-8121/ac1dc1
|View full text |Cite
|
Sign up to set email alerts
|

N-dimensional Smorodinsky–Winternitz model and related higher rank quadratic algebra SW(N)

Abstract: The N-dimensional Smorodinsky–Winternitz system is a maximally superintegrable and exactly solvable model, being subject of study from different approaches. The model has been demonstrated to be multiseparable with wavefunctions given by Laguerre and Jacobi polynomials. In this paper we present the complete symmetry algebra of the system, which it is a higher-rank quadratic one containing the recently discovered Racah algebra as subalgebra. The substructures of distinct quadratic algebras and their related … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In order to derive the spectrum algebraically, we demonstrate the existence of a set of subalgebra structures Q i (3), i = 1, 2, involving three generators and compared them with the quadratic algebra Q(3) presented by Daskaloyannis in the context of 2D superintegrable systems [39]. We recall briefly this algebraic method for two subalgebras Q i (3), i = 1, 2 which involves three operators {A i , B i , C i } for i = 1, 2 and [A i , A j ] = 0, for all i, j [30]. They are close to form the following quadratic algebras,…”
Section: Quadratic Symmetry Algebramentioning
confidence: 99%
See 1 more Smart Citation
“…In order to derive the spectrum algebraically, we demonstrate the existence of a set of subalgebra structures Q i (3), i = 1, 2, involving three generators and compared them with the quadratic algebra Q(3) presented by Daskaloyannis in the context of 2D superintegrable systems [39]. We recall briefly this algebraic method for two subalgebras Q i (3), i = 1, 2 which involves three operators {A i , B i , C i } for i = 1, 2 and [A i , A j ] = 0, for all i, j [30]. They are close to form the following quadratic algebras,…”
Section: Quadratic Symmetry Algebramentioning
confidence: 99%
“…Nowadays, the search for arbitrary dimensional quantum superintegrable systems and their higher-order constants of motion is a paramount research area (see for example [15][16][17][18][19][20][21][22][23][24]). In the context of the algebraic perspective, the higher-order polynomial algebras with structure constants of certain Casimir invariants are constructed by using the integrals of the d-dimensional superintegrable systems [25][26][27][28][29][30]. However, the classification of 3D superintegrable Hamiltonian systems is still an active field of research in particular for nondegenerate quantum superintegrable systems and their symmetry algebras [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…However, the nature of the symmetry algebra of N -dimensional systems still remains a difficult problem, and only recently, with the discovery of R(4) [10] and higher rank Racah algebras R(n) [11,12], further progress has been achieved. It has been pointed out that higher rank quadratic algebras also constitute a powerful tool for the algebraic derivation of spectra [13,14,15,16]. In this context, it has been observed that all classical and quantum systems with coalgebra symmetry admit the Racah algebra as a subalgebra of their symmetry algebra [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that quadratic algebras associated with n-dimensional systems are in general of higher rank [15,16,17,18]. These algebraic structures allow one to obtain useful information on quantum systems and their degenerate spectrum [19]. In most cases, they do not display an obvious basis and thus the construction of their representations is difficult.…”
Section: Introductionmentioning
confidence: 99%